Bimbingan Karir untuk Anak Usia Dini - Shidratul Attika; Lina Eka Retnaningsih (JCE (Journal of Childhood Education), 2025)
Early childhood is in the golden age, so to optimize the potential that exists in him, good stimulation is needed. Stimulation can be given through career guidance services for early childhood. Career guidance for early childhood aims to provide an understanding of the potential that exists in children, as well as to introduce children to various types of jobs and professions that they will undertake in the future according to the development of the times. This article is a literature review, a study of various scientific articles and relevant books. Career guidance services can be provided through modeling or with media that is interesting for early childhood. The success of career guidance for early childhood cannot be separated from the cooperation between teachers, parents, and a supportive environment.